Adverse Impact Of Glaucoma On Psychological Function (Journal of Pharmaceutical Negative Results, 2023)
Background:To compare the quality of life in patients with & without glaucoma using National Eye Institute 25-Item Visual Function Questionnaire (NEIVFQ25). To assess the impact of psychological function in patient with glaucoma.Materials and Methods:This study is Self-administered questionnaire based cross-sectional study with a comparison group. 50 patients with glaucoma and 50 patients without glaucoma were included in the study. Their quality of life, mental health, social function & daily activities were assessed using NEIVFQ25.Results:The mean age of the participants in healthy group & those with glaucoma were 47.2 ± 11.8 & 48.2 ± 13.3 respectively. The p value was 0.72, both the groups were comparable in terms of age distribution. Questionnaire contains 3 parts, PART 1 of the questionnaire was about general health and vision. It was seen that glaucoma patients had a significantly poor general health and vision than the healthy controls (p value <0.01). The PART 2 was about difficulty with activities. It was seen that glaucoma patients had a significantly higher visual difficulty with activities than the healthy controls (p value <0.01). The PART 3 was about responses to vision problems. It was seen that glaucoma patients had a significantly similar response to visual problems as that of healthy participants (p value <0.01).Conclusion:Glaucoma patients dependency rate on others is on higher side. It raises a question whether along with routine ophthalmological evaluation we need a psychological evaluation as well.